The role of hydrogenotrophic methanogens in an acidogenic reactor - Huang, Wenhai (Nanyang Technological University, 2020)
Two-phase anaerobic degradation, compared to single-stage anaerobic degradation, has the potential for higher stability, efficiency and biogas production. The acidogenic phase, as the first phase, not only provides the necessary substrate for the next phase, i.e. the methanogenic phase, it also helps to maintain stability of the whole process. Methanogens, especially hydrogenotrophic methanogens, not only keep a proper hydrogen partial pressure but also behave as syntrophic partner to acetogens and acetate-oxidizing bacteria in various biochemical reactions in the acidogenic phase. A laboratory-scale two-phase anaerobic sequencing batch reactor system was studied to investigate the effects of pH shock on performance and microbial community structures in the reactors and batch studies. Results showed that pH shock caused increase in hydrogen content, low production of VFA and decrease of the hydrogenotrophic methanogen population. However, recovery of pH did not result in immediate recovery of acidogenic reactor performance. The recovery of acidogenic reactor performance only occurred with recovery of the hydrogenotrophic methanogen population and decrease of hydrogen. These observations indicated hydrogenotrophic methanogen helped to maintain a low hydrogen presence in the acidogenic reactor which would then better ensure healthy VFA production. To investigate if external hydrogenotrophic methanogens could also help ease the hydrogen stress on VFA production in the acidogenic reactor at low pH, a laboratory-scale reactor designed to enrich hydrogenotrophic methanogens (RH) was incorporated into the two-phase anSBR system. pH of the acidogenic reactor was maintained at 4.5 to inhibit the resident hydrogenotrophic methanogen in the acidogenic reactor and encourage hydrogen production. Results showed that RH could effectively consume the hydrogen and improve VFA production in acidogenic reactor which enhanced overall performance of the two-phase anSBR. The findings indicated hydrogenotrophic methanogens play an important role in the acidogenic reactor. Maintaining proper methanogenic activity internally or externally for the acidogenic phase is essential to better ensuring an efficient performance of the overall two-phase anaerobic system.